Quantitative Proteomics Analysis of Macrophage Rafts Reveals Compartmentalized Activation of the Proteasome and of Proteasome-mediated ERK Activation in Response to Lipopolysaccharide - Dhungana, Suraj; Merrick, B. Alex; Tomer, Kenneth B.; Fessler, Michael B. (Molecular and Cellular Proteomics, 2009)
Lipopolysaccharide (LPS), a glycolipid component of the outer membrane of Gram-negative bacteria, is a potent initiator of the innate immune response of the macrophage. LPS triggers downstream signaling by selectively recruiting and activating proteins in cholesterol-rich membrane microdomains called lipid rafts. We applied proteomics analysis to macrophage detergent-resistant membranes (DRMs) during an LPS exposure time course in an effort to identify and validate novel events occurring in macrophage rafts. Following metabolic incorporation in cell culture of heavy isotopes of amino acids arginine and lysine ([(13)C(6)]Arg and [(13)C(6)]Lys) or their light counterparts, a SILAC (stable isotope labeling with amino acids in cell culture)-based quantitative, liquid chromatography-tandem mass spectrometry proteomics approach was used to profile LPS-induced changes in the lipid raft proteome of RAW 264.7 macrophages. Unsupervised network analysis of the proteomics data set revealed a marked representation of the ubiquitin-proteasome system as well as changes in proteasome subunit composition following LPS challenge. Functional analysis of DRMs confirmed that LPS causes selective activation of the proteasome in macrophage rafts and proteasome inactivation outside of rafts. Given previous reports of an essential role for proteasomal degradation of IkappaB kinase-phosphorylated p105 in LPS activation of ERK mitogen-activated protein kinase, we tested for a role of rafts in compartmentalization of these events. Immunoblotting of DRMs revealed proteasome-dependent activation of MEK and ERK specifically occurring in lipid rafts as well as proteasomal activity upon raft-localized p105 that was enhanced by LPS. Cholesterol extraction from the intact macrophage with methyl-beta-cyclodextrin was sufficient to activate ERK, recapitulating the LPS-IkappaB kinase-p105-MEK-ERK cascade, whereas both it and the alternate raft-disrupting agent nystatin blocked subsequent LPS activation of the ERK cascade. Taken together, our findings indicate a critical, selective role for raft compartmentalization and regulation of proteasome activity in activation of the MEK-ERK pathway.